Економічна природа та причини формування державного боргу - Федорович, Ірина Михайлівна; Fedorovych, Irina (ТНЕУ, 2015)
Охарактеризовано економічну природу та місце державного боргу в фінансовій системі держави. Розглянуто концептуальні підходи до визначення змісту поняття «державний борг» на основі синтезу вітчизняної та світової фінансової думки. Проаналізовано основні причини, що впливають на формування державного боргу. Economic nature and the place of the public debt were characterized in the financial system of the state. Conceptual approaches to the definition of what constitutes "public debt" we're reviewed and based on the synthesis of national and global financial view that takes into account the causes and conditions of its formation in two ways: 1) as a certain amount of debt associated with the budget deficit; 2) as a combination of financial and credit relations arising in connection with the movement of capital. This approach takes into account the multidimensional concept of public debt and serves as the theory of debt finance. The article suggests to interpret "public debt" as a set of economic relations between the state and its creditors over the formation, repayment and servicing of government debt and other liabilities for guarantees granted by the State in accordance with applicable law and international treaties. Unlike existing approach allows to take into account the structural balance of debt financial instruments in conjunction with public debt management. The basic reasons were analyzed that influence the formation of public debt.
Economic nature and causes of formation of government debt
Keywords: державний борг; гарантований державою борг; боргове навантаження; бюджетний дефіцит; складові формування державного боргу; видатки на обслуговування державного боргу; public debt; government guaranteed debt; debt burden; budget deficit; components forming the national debt; cost of servicing the public debt